The role of the β-1,6-endoglucanase gene vegB in physiology and virulence of Verticillium dahliae - EBOIGBE, Lugard; TZIMA, Aliki; PAPLOMATAS, Epaminondas; TYPAS, Milton (Phytopathologia Mediterranea, 2014)
The β-1,6-endoglucanase gene (vegB) of Verticillium dahliae was isolated using a genome walking technique. Nucleotide and deduced amino acid sequences of the gene showed high identity with the PAN1 sequence deposited at the Verticillium genome database (Broad Institute), but significant differences in intron numbers and sites of insertion. Detailed in silico analysis, accompanied by sequencing of both genomic and cDNA, as well as RT-PCR experiments, provided the correct size of the gene and the exact number, length and positions of introns. The putative protein of this gene was compared with corresponding β-1,6-endoglucanases from other fungi, and sequences were used to construct a phylogenetic tree. A clear differentiation between enzymes derived from plant pathogenic and mycoparasitic fungi was observed, fully supported by bootstrap data. An internal fragment (1.2kb) of vegB was used to disrupt the wild-type gene of a V. dahliae tomato race 2 strain, and the mutant strain, vegB-, was tested for pathogenicity on tomato plants. Results showed a small but constant reduction in disease symptoms only on eggplants for the vegB- strain in comparison with the wild type. Growth on minimal medium supplemented with different carbon sources showed reduced ability of the mutant to breakdown cellulose, whereas growth on glucose, pectin and sucrose was similar to the wild type.